Conditions mimicking acute ST-segment elevation myocardial infarction in patients referred for primary percutaneous coronary intervention - Gu, Y. L.; Svilaas, T.; van der Horst, I. C. C.; Zijlstra, F. (Netherlands heart journal, 2008)
BACKGROUND/OBJECTIVES.: A rapid diagnosis of ST-segment elevation myocardial infarction (STEMI) is mandatory for optimal treatment. However, a small proportion of patients with suspected STEMI suffer from other conditions. Although case reports have described these conditions, a contemporary systematic analysis is lacking. We report the incidence, clinical characteristics and outcome of patients with suspected STEMI referred for primary percutaneous coronary intervention (PCI) with a final diagnosis other than STEMI. METHODS.: From January 2004 to July 2005, 820 consecutive patients were included with suspected STEMI who were referred for primary PCI to a university medical centre, based on a predefined protocol. Clinical characteristics, final diagnosis and outcome were obtained from patient charts and databases. RESULTS.: In 19 patients (2.3%), a final diagnosis other than myocardial infarction was established: coronary aneurysm (n=1), (myo)pericarditis (n=5), cardiomyopathy (n=2), Brugada syndrome (n=1), aortic stenosis (n=1), aortic dissection (n=3), subarachnoidal haemorrhage (n=2), pneumonia (n=1), chronic obstructive pulmonary disease (n=1), mediastinal tumour (n=1), and peritonitis after recent abdominal surgery (n=1). These patients less often reported previous symptoms of angina (p<0.001), smoking (p<0.05) and a positive family history of cardiovascular diseases (p<0.05) than STEMI patients. Mortality at 30 days was 16%. CONCLUSION.: A 2.3% incidence of conditions mimicking STEMI was found in patients referred for primary PCI. A high clinical suspicion of conditions mimicking STEMI remains necessary. (Neth Heart J 2008;16:325-31.).